Effects of potassium sodium niobate (KNN) thickness on biaxial non-resonant microelectromechanical systems (MEMS) mirror performance - L. Mollard; C. Dieppedale; A. Hamelin; R. Liechti; G. Le Rhun (Journal of Sensors and Sensor Systems)
This work presents the results obtained with potassium sodium niobate (KNN) biaxial non-resonant microelectromechanical systems (MEMS) mirrors manufactured on a 200 mm silicon substrate. These MEMS mirrors feature various reflector dimensions for the squared shape, ranging from 0.5 × 0.5 to 2 × 2 mm2, and incorporate sputtered potassium sodium niobate ((K0.35Na0.65)NbO3) thin-film piezo-motors from Sumitomo Chemical, with thicknesses varying from 0.5 to 1.5 µm. A comparison of the mirror's performance and static deformation as a function of KNN thickness will be presented and discussed. The results obtained with these non-resonant mirrors, all fabricated using a collective 200 mm silicon manufacturing process, exhibit the following: (a) an arm deformation of 50 to 80 µm corresponding to an estimated tensile residual stress of approximately 120 MPa in the KNN layer, (b) the same level of performance for the 0.5 µm thick lead zirconate titanate (PZT) and KNN at 10 V, and (c) an optical angle up to 8.5° at 40 V for the 2 × 2 mm2 mirror design with 1.5 µm thick KNN. These results indicate that the MEMS mirrors fabricated with the KNN lead-free piezoelectric material offer state-of-the-art performances and open potential applications in a wide range of fields from light detection and ranging (lidar) systems to biomedical applications, thanks to the full biocompatibility of the KNN material.